Diskursus Pendidikan Multikultural di Lembaga Pendidikan Dasar dan Menengah Islam Indonesia 2016-2021 - Zaenal Muttaqin (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
This article explores how multicultural education at the Indonesian Islamic primary and secondary education levels and its implementation is investigated by scholars in the country. The research questions in this article are formulated in two questions, namely 1) How is the concept of multicultural education in Islamic educational institutions defined in the last six years (2016-2021)? 2) How is the implementation of multicultural education in various aspects of education at primary and secondary Islamic educational institutions in this period? This research utilizes the Systematic Literature Review (SLR) method which is considered very helpful for this research model because it requires three stages, namely planning (planning), conduct (conducting), and reporting (reporting). As a result, 89 data articles have been presented by scholars in discussing multicultural education in Islamic primary-secondary education institutions throughout this period. In detail, 33 articles were found that were considered relevant to the research question, of which 21 data articles discussed the translation of concepts or discourses about multicultural education and 11 other data were more focused on analyzing multicultural education in Islamic education at the implementation level. Thus, multicultural education in Islamic educational institutions has become a topic that has attracted a lot of study by Indonesian scholars in the last six years.